PAINT I: the effect of art therapy in preventing and managing delirium among hospitalized older adults in the PAINT I study—a proof-of-concept trial - Singler, Katrin; Masuch, J.; Lim, S.; Habboub, B.; Gosch, M. (European Geriatric Medicine, 2022)
Background: Delirium is common among older hospitalized patients and is regarded as a negative outcome parameter. Non-pharmacological strategies have been shown to be effective in the prevention and management of delirium. This study aimed to determine the effectiveness of art therapy as part of a multicomponent intervention in preventing and managing delirium in hospitalized older patients. Methods: 138 patients at risk of developing delirium were included and received art therapy twice daily for 25 min using a mobile atelier. 107 participants were included in the final analysis (N = 53 intervention, N = 54 control). The primary outcome was the effectiveness of art therapy in preventing delirium. The secondary outcome was to determine its impact on duration of delirium in patients with existing delirium. Delirium was assessed using the Nursing delirium Screening Scale (Nu-DESC). Results: 8 patients (7.5%) developed new onset delirium after admission, equally distributed among control and intervention group. Therefore, no valid statistical analysis could be performed. There was a statistically non-significant decrease in the duration of delirium in the intervention group (4 days, IQR 2.25–8.75) compared to the control group (7 days, IQR 5-10), Mann-Whitney-U-Test p-value = 0.26. After stratifying by dementia diagnosis on admission, the non-significant decrease in duration of delirium in the intervention group was more apparent in patients without dementia. Conclusion: Findings from this study showed that the integration of art therapy as part of a multicomponent intervention in delirium management is feasible, and can reduce duration of delirium among hospitalized older adults.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Art therapy; Communication; Delirium; Non-pharmacological intervention; Prevention